Prevalence and antimicrobial resistance assessment of subclinical mastitis in milk samples from selected dairy farms - Marimuthu, Murugaiyah; Abdullah, Faez Firdaus Jesse; Mohammed, Konto; Sarvananthan Poshpum, Sangeetha; Adamu, Lawan; Osman, Abdinasir Yusuf; Abba, Yusuf; Tijjani, Abdulnasir (Science Publications, 2014)
This study was conducted in order to determine the prevalence and bacteriological assessment of subclinical mastitis and antimicrobial resistance of bacterial isolates from dairy cows in different farms around Selangor, Malaysia. A total of 120 milk samples from 3 different farms were randomly collected and tested for subclinical mastitis using California Mastitis Test (CMT), as well as for bacterial culture for isolation, identification and antimicrobial resistance. The most prevalent bacteria was Staphylococcus sp. (55%), followed by Bacillus sp., (21%) and Corynebacterium sp., (7%), Yersinia sp. and Neisseria sp. both showed 5% prevalence, other species with prevalence below 5% are Acinetobacter sp., Actinobacillus sp., Vibrio sp., Pseudomonas sp., E.coli, Klebsiella sp. and Chromobacter sp. Selected Staphylococcus sp. showed a mean antimicrobial resistance of 73.3% to Ampicillin, 26.7% to Penicillin, Methicillin and Compound Sulphonamide each, 20% to Oxacillin, Amoxycillin and Cefuroxime, 13.3% to Polymyxin B, Erythromycin, Ceftriaxone and Azithromycin and 6.7% to Streptomycin, Clindamycin, Lincomycin and Tetracycline each. This study indicates the need for urgent and effective control measures to tackle the increase in prevalence of subclinical mastitis and their antimicrobial resistance in the study area.